Analysis of Nursing Clinical Practice Using Relating Therapy Intervention to Reduce Auditory Hallucination Symptoms - Nuraini Yulianti; Arief Budiman; Linda Dwi Novial; Dwi Rahmah Fitriani (Jurnal Kesehatan Cendikia Jenius, 2026)
Auditory hallucinations are one of the most common and disruptive symptoms experienced by individuals Auditory hallucinations are one of the positive symptoms of schizophrenia that significantly affect patients’ cognitive processes, emotional stability, and social interactions, making comprehensive nursing care essential. This study aims to analyze the effectiveness of Relating Therapy (RT) as an innovative intervention in reducing the signs and symptoms of auditory hallucinations among patients in the Elang Ward of Atma Husada Mahakam Samarinda Mental Hospital. This research employed a case study design using a psychiatric nursing care approach on a patient diagnosed with paranoid schizophrenia. Data were collected through clinical observation, interviews, and the Auditory Hallucination Rating Scale (AHRS) over a nine-day intervention period, then analyzed descriptively to identify changes in frequency, intensity, and emotional distress related to hallucinations. The results demonstrated a significant decrease in AHRS scores from 24 (severe hallucinations) to 5 (mild hallucinations) after six sessions of Relating Therapy, along with improved self-control, reduced psychological distress, and more assertive responses toward hallucinatory voices. This study concludes that Relating Therapy is effective as a non-pharmacological intervention in reducing auditory hallucination symptoms and is recommended for integration into clinical psychiatric nursing practice, with a suggestion for its continued application to enhance patient outcomes.